Pengaruh God Consciouness dan Karakter Wirausahawan terhadap Keberhasilan Usaha di Langsa Town Square - Safwan_kamal Safwan; Nurjannah Nurjannah; Rahmah Susanti (Program Pascasarjana IAIN Langsa, 2021)
This study aims to determine the effect of god consciousness and entrepreneur behavior on sales success in Langsa Town Square. The method used is a quantitative approach. Data was collected using a questionnaire with a sample of 64 respondents and the sampling technique used probability sampling. The data analysis method used is multiple linear regression analysis using SPSS software version 16.0. This study uses a Likert scale measurement. The results of this study are based on a partial test, the god consciousness variable has an effect on sales success with a significant value of 0.002 which is smaller than the value of 0.05. The entrepreneur behavior variable has an effect on business success as indicated by a significant value of 0.000 which is smaller than 0.05. simultaneously, these two variables have a significant effect on business success and the value of R square is 0.739 or 73.9%.